TYPES OF TEACHER TALK TO SUPPORT STUDENTS’ ACTIVENESS IN ONLINE CLASSROOM - Ana, Rina Yuli; Dewi, Ratna; Amin, Bahrun (Elite : English and Literature Journal, 2021)
This study concerned with teacher talk in online classroom. The interaction between teacher and students are analyzed into types of teacher talk. The aim of this study is to find it types of teacher talk to support students’ activeness in online classroom. Descriptive qualitative design was used as research methodology. The researcher was as nonparticipant observer in online class. There were two teachers involved as research participants. The participants conducted online class by using Zoom Application. Video recording from Zoom was analyzed by applying three steps, which consisted of reading or memoing data, describing data, and classifying data. In analyzing the data, the researcher referred to types of teacher talk by Brown who classified teacher talk into seven types. The research findings found there were five types of teacher talk in online classroom. Those are praising and encouraging, accepting ideas of students, asking questions, lecturing, and giving direction. These types found are used to support the students’ activeness in online classroom. Therefore, active and passive students are related to teacher talk. This study is implied to be used as reference to be applied by the teachers to keep the students active in online classroom.